CORRELATES OF SELF-CONCEPT, ATTITUDE AND MATHEMATICS PERFORMANCE OF SENIOR SECONDARY SCHOOL STUDENTS IN NIGERIA - Kojigili, Stephen Tizhe (PEOPLE: International Journal of Social Sciences, 2020)
The study investigated the correlates of senior students’ mathematics self-concept, attitude, and mathematics performance in secondary school level of Nigeria. The population comprised all the secondary school students from the six states in Northeast, Nigeria. From the population, a total of 589 students were sampled from 18 schools purposively selected from four out of the six states in the zone. The instruments employed for the data collections were Mathematics Achievement Test (MAT) and a Mathematics Self-concept and Attitude Scale (MSCAS). The instruments were validated and the reliability was determined through test re-test method. Using Cronbach alpha analysis, high reliability coefficients of 0.83and 0.915 were obtained for MAT and MSCAS respectively. The statistical tools used in testing the hypotheses were t-test, Analysis of Variance (ANOVA), correlation, and multiple regression analysis. The results of the findings revealed that the students’ self-concept correlates significantly with their attitude; and relationship exists significantly among students’ self-concept, attitude and their performance. It was recommended among other things that students’ mathematics self-concept and attitude be improved in schools by making the teaching of mathematics practical oriented such that students see it interesting and pleasurable.